2010
DOI: 10.1007/978-3-642-15020-3_2
|View full text |Cite
|
Sign up to set email alerts
|

MEDCollector: Multisource Epidemic Data Collector

Abstract: Abstract. This paper analyzes the requirements and presents a novel approach to the development of a system for epidemiological data collection and integration based on the principles of interoperability and modularity. Accurate and timely epidemic models require the integration of large, fresh datasets. Thus, from an e-science perspective, collected data should be shared seamlessly across multiple applications. This is addressed by our approach, MEDCollector, trough workflow design enables the extraction of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Prior work has linked news stories with stock prices [19][20][21] and used web search or social media data to forecast labor markets [22][23][24][25][26], consumer behavior [27,28], automobile demand, vacation destinations [15,29]. Research on social media, search, and surfing behavior have been shown to signal emerging public health problems [30][31][32][33][34][35][36][37]; although for a cautionary tale see [38]. And recent efforts have even been made towards leveraging Twitter to detect and track earthquakes in real-time detection faster than seismographic sensors [39][40][41].…”
Section: Predicting the Presentmentioning
confidence: 99%
“…Prior work has linked news stories with stock prices [19][20][21] and used web search or social media data to forecast labor markets [22][23][24][25][26], consumer behavior [27,28], automobile demand, vacation destinations [15,29]. Research on social media, search, and surfing behavior have been shown to signal emerging public health problems [30][31][32][33][34][35][36][37]; although for a cautionary tale see [38]. And recent efforts have even been made towards leveraging Twitter to detect and track earthquakes in real-time detection faster than seismographic sensors [39][40][41].…”
Section: Predicting the Presentmentioning
confidence: 99%